Hypoxia-Inducible Factor 1-Alpha and Glucose Metabolism during Cardiac Remodeling Progression from Hypertrophy to Heart Failure - Sant’Ana, Paula Grippa [UNESP]; Tomasi, Loreta Casquel de [UNESP]; Murata, Gilson Masahiro; Vileigas, Danielle Fernandes [UNESP]; Mota, Gustavo Augusto Ferreira [UNESP]; Souza, Sérgio Luiz Borges de [UNESP]; Silva, Vitor Loureiro [UNESP]; Campos, Livia Paschoalino de [UNESP]; Okoshi, Katashi [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (MDPI, 2023)
In pathological cardiac hypertrophy, the heart is more dependent on glucose than fatty acids. This shift in energy metabolism occurs due to several factors, including the oxygen deficit, which activates hypoxia-inducible factor-1α (HIF-1α), a critical molecule related to glucose metabolism. However, there are gaps regarding the behavior of key proteins in the glycolytic pathway and HIF-1α during the transition from hypertrophy to heart failure (HF). This study assesses the hypothesis that there is an early change and enhancement of HIF-1α and the glycolytic pathway, as well as an association between them during cardiac remodeling. Sham and aortic stenosis Wistar rats were analyzed at 2, 6, and 18 weeks and in HF (n = 10–18). Cardiac structure and function were investigated by echocardiogram. Myocardial glycolysis, the aerobic and anaerobic pathways and glycogen were analyzed by enzymatic assay, Western blot, and enzyme-linked immunosorbent assay (ELISA). The following were observed: increased left ventricular hypertrophy; early diastolic function change and severe systolic and diastolic dysfunction in HF; increased HIF-1α in the 2nd week and in HF; precocious alteration and intensification of glycolysis with a shift to anaerobic metabolism from the 6th week onwards; association between HIF-1α, glycolysis, and the anaerobic pathway. Our hypothesis was confirmed as there was an early change and intensification in glucose metabolism, alteration in HIF-1α, and an association between data during the progression from hypertrophy to heart failure.
Keywords: aortic stenosis; cardiac remodeling; glucose metabolism; HIF-1α; rats